Determinants of Chronic Energy Deficiency among Adolescent Girls: A Cross-Sectional Study at SMP Negeri 44 Surabaya - Jazilah Nur Arifah; Fahmi Hafid; Ani Intiyati; Taufiqurrahman Taufiqurrahman (Journal of Nutrition Explorations, 2025)
Chronic Energy Deficiency (CED) is a nutritional issue with long-term implications for the health and productivity of adolescent girls. This study aimed to analyze the determinants associated with CED among seventh- and eighth-grade students at SMP Negeri 44 Surabaya. Using an analytical observational design with a cross-sectional approach, the study involved 69 respondents selected via stratified random sampling. Data were collected through mid-upper arm circumference measurements, dietary intake questionnaires, assessments of nutritional knowledge, physical activity, and sociodemographic factors. Statistical analysis was conducted using the Chi-square test. The results showed a CED prevalence of 81.2%, with most respondents experiencing deficits in energy (89.9%) and carbohydrate intake (98.6%). Significant associations were found between energy intake (p=0.012), carbohydrate intake (p=0.037), and nutritional knowledge (p=0.015) with CED status. Other variables, including protein and fat intake, physical activity, parental education and income, and body image perception, were not significantly associated. The study concludes that low energy and carbohydrate intake, along with limited nutritional knowledge, are key contributors to CED. School-based nutritional interventions and parental involvement are essential strategies to prevent CED in adolescents.